Modelling of freight flows distribution at the transport terminal - Baublys, Adolfas (Transport, 2004)
The task model has been formulated for users of freight flows at a distribution transport terminal, which enables gauging vehicles possibilities (dimensions, carrying capacity), delivery time limitations, resources of vehicle time and general costs. The synthesis of the topological structure of the freight road transport regional system has been performed. It enables the evaluation of an impact on the functioning of the system exercised by various structural system characteristics, thus improving the quality of project solutions at the stage of synthesis of the system structure.First Published Online: 27 Oct 2010